This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 7. Find the Laplace transforms of the following functions: (a) x ( t ) = [ e-2 t + te-3 t ] u ( t ) (b) x ( t ) = u ( t )-2 u ( t-1) + u ( t-2) 8. Find the inverse Laplace transforms of the following functions: (a) X ( s ) = ( s +1) ( s +2)( s +4) . (b) X ( s ) = s +4 ( s +2) 2 +4 1...
View Full Document
This note was uploaded on 01/01/2012 for the course ECEN 314 taught by Professor Halverson during the Spring '08 term at Texas A&M.
- Spring '08